Numerical simulation of progressive sand production of open-hole completion borehole in heterogeneous igneous formation. (February 2022) - Ma, Tianshou; Qiu, Yi; Zhang, Yun; Liu, Yang
Abstract: Sand production can occur during hydrocarbon production, which poses a significant issue for continued oil and gas production. The existing finite element simulation of sand production usually assumes that the formation rock is a homogeneous medium. However, the actual formation is usually a heterogeneous natural material; during the testing and production process, sand production is a long-term, continuous, and gradual process. The wellbore pressure change has an important influence on sand production. Therefore, this study presents a numerical simulation method for progressive sand production in inhomogeneous formations. First, based on the theory of elastic damage mechanics, considering the heterogeneous characteristics of formation rock physical properties and mechanical parameters, a steady-state coupled hydraulic-mechanical-damage finite element model was established. Second, a multi-layer finite element method with multiple iterations was used to solve the model. After each iteration, the material mechanical parameters were updated to simulate the damage unit equivalent, which simulated the progressive sand production process. Finally, sand production during testing in typical igneous formations was analyzed, the influences of heterogeneity, progressive failure process, and wellbore pressure change are discussed in terms of progressive sand production, and systematic parametric simulation and analysis were conducted. The results show that the sand production zone is controlled by the formation rock heterogeneity and progressive failure process. The results indicate that the sensitivity of the normalized yield zone area (NYZA) to mean parameter value can be ranked as follows: cohesion > Poisson's ratio > Young's modulus > internal friction angle, and the sensitivity of the NYZA to standard of deviation parameter value can be ranked as follows: internal friction angle > Poisson's ratio > Young's modulus > cohesion.